2008
DOI: 10.1590/s0100-06832008000300019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da biodiversidade de rizóbios simbiontes do feijoeiro (Phaseolus vulgaris L.) em Santa Catarina

Abstract: RESUMOOs solos brasileiros, em geral, apresentam uma população abundante de rizóbios capazes de nodular e fixar N 2 em simbiose com o feijoeiro (Phaseolus vulgaris L.); contudo, a diversidade dessas bactérias ainda é pouco conhecida. Este estudo teve por objetivo conhecer a biodiversidade de microssimbiontes do feijoeiro em Santa Catarina e, para isso, foram obtidos 117 isolados de nódulos de plantas coletadas em campo, em 23 áreas do extremo oeste, do meio oeste e do planalto sul catarinense. Com base nos atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
1
11
1
3
Order By: Relevance
“…The groups formed had between 26 % (group D) and 48 % (group C) of similarity. Genetic differences between rhizobium isolates using ARDRA were also observed by Han et al (2008), Stocco et al (2008), Ruiz-Díez et al (2009) and Sui et al (2009).…”
Section: Amplified Ribosomal Dna Restriction Analysis (Ardra)mentioning
confidence: 61%
See 1 more Smart Citation
“…The groups formed had between 26 % (group D) and 48 % (group C) of similarity. Genetic differences between rhizobium isolates using ARDRA were also observed by Han et al (2008), Stocco et al (2008), Ruiz-Díez et al (2009) and Sui et al (2009).…”
Section: Amplified Ribosomal Dna Restriction Analysis (Ardra)mentioning
confidence: 61%
“…trifolii (BR 7606) from R. gallicum (BR 528), which appeared in this group with 100 % similarity between them. Studying the biodiversity of bean symbiont rhizobium, Stocco et al (2008) also found no distinction between R. leguminosarum and R. giardinii using three enzymes (HhaI, HpaII and RsaI). The strains R. galegae (BR 10055) and R. giardinii (BR 529) and isolate 373-6 appeared isolated in this group, with similarities of 42 and 40 %, respectively, with the two subgroups formed.…”
Section: Amplified Ribosomal Dna Restriction Analysis (Ardra)mentioning
confidence: 98%
“…Among the cultivated species, studies conducted in Brazil have already examined the genetic variability of rhizobia of legumes such as pigeonpea (Costa et al, 2014), peanuts (Lyra et al, 2013;TorresJúnior et al, 2014), common beans (Stocco et al, 2008), among others. This technique is also used to examine the variability of strains isolated from native plants such as bromeliad (Giongo et al, 2013), wild rice (Fernandes Júnior et al, 2013) and legumes (Granada et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic characterization is the basis of polyphasic taxonomy and, together with molecular techniques, has contributed to an improved understanding of the physiology and genetic diversity of rhizobia (Zerhari et al, 2000;Fall et al, 2008;Rasul et al, 2012). Among the molecular characterization techniques, fingerprinting by means of Box-PCR generated profiles have been used to examine the diversity of diazotrophic bacteria associated with the (Stocco et al, 2008;Costa et al, 2014;Torres-Júnior et al, 2014) and native species (Fernandes Júnior et al, 2013;Granada et al, 2014) from Brazil. This simple and low-cost technique allows the discrimination among several rhizobial isolates and reference strains, making possible a fast fingerprinting and selection of bacterial isolates.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos solos com histórico de cultivo de feijão contém rizóbios nativos que podem interferir no estabelecimento e na eficácia das estirpes inoculadas, reduzindo as respostas à inoculação (Vlassak et al, 1996;Vargas et al, 2000;Raposeiras et al, 2006 (Mostasso et al, 2002;Raposeiras et al, 2006), na Região Sul Hungria et al, 2003;Stocco et al, 2008) e na Região Sudeste (Soares et al, 2006;Lombardi et al, 2009;Torres et al, 2009). Além dessas estirpes de Rhizobium, grande número de isolados classificados como Sinorhizobium sp.…”
Section: Introductionunclassified